PROFIL PEMECAHAN MASALAH SISWA SMP NEGERI 1 PALASA DALAM PROFIL PEMECAHAN MASALAH TURUNAN FUNGSI ALJABAR SISWA KELAS XI IPA SMA NEGERI 1 WITA PONDA: Profile Of Problem Solving Of Derived Algebraic Functions Of The 11th Grade Of Science Students At Sma Negeri 1 Wita Ponda - Ni Made Luh Kerti; Sudarman Bennu; Anggraini Anggraini (Universitas Tadulako, 2025)
This study aims to describe the profile of solving problems of derivatives of algebraic functions. This type of research is a qualitative research with a qualitative descriptive approach based on the problem solving stages of Polya. The determination of the research subject was based on the results of daily mathematics tests for the 2021/2022 school year and recommendations from the mathematics teacher. Data collection was carried out by giving assignments and interviews. The results of this study indicate that: 1) the stages of understanding the problems of students with high, medium and low mathematical abilities are identifying problem information, namely things that are known and asked through statements and command sentences correctly. 2) the stage of making a problem-solving plan for students with high mathematical abilities uses the concept of derivatives of algebraic functions to correctly determine the speed and acceleration, students with moderate mathematical abilities are right to the wrong speed and acceleration, while students with low mathematical ability to determine the correct speed and acceleration are wrong. 3) the stage of carrying out the problem-solving plan for students with high mathematical abilities carrying out the problem-solving plan correctly, students with mathematical abilities carrying out the problem-solving plan at the right speed but not the right acceleration, while students with low mathematical ability carrying out the problem-solving plan incorrectly. 4) the stage of re-examining the problem solving of students with high mathematical abilities checked again correctly, students with medium and low mathematical abilities did not re-check their answers.